Clinical outcomes and serologic response in solid organ transplant recipients with COVID-19: A case series from the United States - Fung, Monica (Am J Transplant, 2020)
The coronavirus disease 2019 (COVID-19) pandemic caused by SARS coronavirus 2 (SARS-CoV-2) has caused significant morbidity and mortality for patients and stressed healthcare systems worldwide. The clinical features, disease course, and serologic response of COVID-19 among immunosuppressed patients such as solid organ transplant (SOT) recipients, who are at presumed risk for more severe disease, are not well characterized. We describe our institutional experience with COVID-19 among 10 SOT patients, including the clinical presentation, treatment modalities, and outcomes of 7 renal transplant recipients, 1 liver transplant recipient, 1 heart transplant recipient, and 1 lung transplant recipient. In addition, we report the serologic response in SOT recipients, documenting a positive IgG response in all 7 hospitalized patients. We also review the existing literature on COVID-19 in SOT recipients to consolidate the current knowledge on COVID-19 in the SOT population for the transplant community.